“STUDI POTENSI PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) DI DESA” AAN, KABUPATEN KLUNGKUNG PROVINSI BALI - Dwiky Sadha Widiarta, Kadek; Arta Wijaya, I Wayan; Suartika, I Made (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i03.p1, 2021)
Bali has the potential for mini-hydro and micro-hydro power plants of 15 MW. There are 154 rivers and springs scattered in Bali which are used as irrigation for rice fields. Aan Village has an Irrigation Channel, namely Subak Aan Dauh Desa which is sourced from the Tukad Bubuh, which according to observations has a stable flow every year. This study aims to determine the potential of MHP in Aan Village, especially in Subak Aan Dauh Village Irrigation Channel, Tukad Bubuh seen from the condition of the research location, water discharge and head. The methods used in this research are observation, literature study, and interviews. The data is then processed to obtain an estimate of the appropriate power generation based on the water discharge, and head at each location. The results of this study indicate the potential of MHP in the Subak Aan Dauh Desa irrigation channel, Tukad Bubuh, Aan Village, there are 4 research locations with each water discharge of 0,7917 m3/s, 0,7434 m3/s, 0,9612 m3/s, and 0,3198 m3/s, having a head of 0.9 m, 1.1 m, 3 m, and 2 m. The estimated power generation with the assumption that the total efficiency of the 65% is 4.54 kW, 10.42 kW, 18.38 kW, and 4.07 kW. Based on the aspect of determining the type of turbine at each research location, locations 1 and 2 used the Breast Wheel type waterwheel, while locations 3 and 4 used Archimedes Screw turbines.